2006
DOI: 10.1590/s0101-81752006000100021
|View full text |Cite
|
Sign up to set email alerts
|

Biologia reprodutiva e reprodução induzida de duas espécies de Characidae (Osteichthyes, Characiformes) da bacia do São Francisco, Minas Gerais, Brasil

Abstract: Astyanax bimaculatus (Linnaeus, 1758) e Tetragonopterus chalceus Spix & Agassiz, 1829 são duas importantes espécies de peixes forrageiros da bacia do São Francisco. Espécimes destas duas espécies foram submetidos à indução da desova através de hipofisação, para observação de aspectos reprodutivos e obtenção de subsídios para definição de protocolo de reprodução artificial. Machos e fêmeas receberam dose única de extrato bruto de hipófise de carpa comum (6 mg/kg de peixe). A extrusão de ovócitos foi realiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 5 publications
5
43
0
13
Order By: Relevance
“…During the experimental period, the mean values of temperature 28.67±0.73 o C, pH 6.65±0.68, and dissolved oxygen 5.23±0.85 mg L -1 were within the range considered acceptable for fish growth, according to Sato et al (2006).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…During the experimental period, the mean values of temperature 28.67±0.73 o C, pH 6.65±0.68, and dissolved oxygen 5.23±0.85 mg L -1 were within the range considered acceptable for fish growth, according to Sato et al (2006).…”
Section: Resultsmentioning
confidence: 85%
“…This kind of fish accepts artificial feeding with ease, and has good potential for aquaculture. Its commercial importance is relevant as baits in sport fishing, appetizer and as ornamental fish (Sato et al, 2006). Lambari is omnivorous, and can reach 10.9 cm and 42 g. Depending on environmental conditions, lambari´s spawning can be whole or split (Sato et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest correlation was found between fecundity and gonad mass in the headwaters and between fecundity and body length in the flood area. Several studies have identified a positive relationship between the number of oocytes and fish size (Adite et al, 2006;Brickle et al, 2005;Magalhães et al, 2003;Mazzoni & Silva, 2006;Moffett et al, 2006;Sato et al, 2006;Tarkan, 2006;Martins-Queiroz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Esta espécie, de pequeno porte, aceita alimentação artificial com bastante facilidade e apresenta bom potencial para a aqüicultura, podendo ser utilizados como iscas em pesca esportivas, como petiscos e como peixes ornamentais (SATO et al, 2006). Além disso, os lambaris possuem grande importância ecológica ao fazerem parte da dieta de vários vertebrados e serem dispersores secundários de sementes auxiliando na preservação das matas ciliares (FERNANDES; MARTINS-SANTOS, 2004).…”
Section: Efeito De Diferentes Intensidades De Luz Sobre a Resposta Aounclassified